Assessing preschool English learners' receptive and expressive language ability to inform instruction. Issue 5 (28th May 2022) - Kim, Ahyoung Alicia; Chapman, Mark; West, Gordon Blaine; Zheng, Bingjie; Cranley, M. Elizabeth
ABSTRACT: This study explores how preschool educators could assess dual language learners' (DLLs) English language abilities using formative instruments in school settings. It specifically examines (1) DLLs' receptive and expressive language proficiencies measured using the instruments and (2) educators' perceived usefulness of them for informing instruction. Participants were 139 preschool DLLs ( M  = 4;9) and 37 preschool educators from four countries (Argentina, Chile, China, and US). DLLs' families completed a questionnaire on the child's language background, indicating the child's home language and English abilities. Educators measured DLLs' English proficiency using adult–child co-play activities and language observations. Afterwards, educators completed a survey regarding the usefulness of these instruments. Findings show that DLLs' receptive English language ability was higher than and significantly correlated with their expressive ability in their home language and English. Also, parents' estimate of their children's English language ability was similar to that of educators. The correlation between DLLs' home language and English proficiencies was statistically significant, but low, indicating that the two languages do not necessarily develop together. Educators found the formative instruments helpful in understanding DLLs' language proficiency and believed that such an understanding could inform their instruction. Results provide implications for assessing DLLs' English language ability using age appropriate instruments.